Development of knowledge, awareness, and practice questionnaire on safety and emergency response and assessing factors associated with diving related illness and injury among recreational scuba divers in Malaysia - Muhammad, Aladin (2024)
Background: Recreational scuba diving, an adventurous sport, poses inherent risks like high-pressure environments and buoyancy changes, impacting divers' well-being. While the undersea journey is captivating, safety hinges on strong foundations in knowledge, awareness, and safety practices. Assessing divers' KAP is crucial, highlighting the need for ongoing improvements. Objectives: To develop and validate a new questionnaire assessing the knowledge, awareness, and practice of safety and emergency response among scuba divers in Malaysia, and to determine factors associated with good KAP. Additionally, the study aims to investigate the prevalence of diving-related injury and illness, along with its associated factors. Methodology: This study, spanning from November 2022 to December 2023, had two phases. Phase one involved 555 scuba divers, aimed to develop and validate a questionnaire using literature review, expert opinions, existing questionnaires, and a theoretical framework. Validation involved item response theory (IRT) for knowledge and exploratory/confirmatory factor analysis (EFA/CFA) for awareness and practice. In phase two, a cross-sectional study surveyed 407 divers from ten centers in Tioman and Perhentian Islands, employing the new questionnaire. Result: A validated 42-item questionnaire, demonstrating good internal consistency (Cronbach’s alpha: 0.77–0.80). Composite reliability, however, fell slightly below the threshold (Raykov’s rho: 0.55–0.71). The model fitness for the knowledge component was confirmed through modified parallel analysis, revealing an RMSEA of 0.02 (95% CI = 0.005, 0.03). Meanwhile, for awareness and practice, the fitness indices were deemed satisfactory: SRMR = 0.04, RMSEA = 0.03–0.04, CFI = 0.98, TLI = 0.96–0.97. In phase two, diving-related injury/illness prevalence was 26.1%, predominantly barotrauma (17.9%). Mishaps were reported at 51.4%, mainly due to equalization problems (40.8%). KAP assessment revealed that 91.8% had good knowledge (mean score: 17.8 (SD=2.08), 93.1% had good awareness (mean score: 4.37, SD=0.41), and 85% exhibited good practice (mean score: 4.11, SD=0.44). Factors associated with good knowledge included education level (adjOR: 3.13; 95% CI: 1.03,9.46; p=0.044) and diving depth (adjOR: 0.40; 95% CI: 0.18,0.90; p=0.027). Dive frequency was a significant factor for good awareness (adjOR: 0.20; 95% CI: 0.05,0.89; p=0.034). Diving-related injury and illness were associated with increasing height (adjOR: 1.37; 95% CI: 1.00,1.88; p=0.050), weight (adjOR: 0.68; 95% CI: 0.46,0.99; p=0.045), elevated BMI (adjOR: 3.14; 95% CI: 1.06,9.30; p=0.039), and certification level (adjOR: 3.78; 95% CI: 1.68,8.49; p=0.001). Mishaps were associated with increased weight (adjOR: 1.03; 95% CI: 1.01,1.05; p=0.008) and certification level (adjOR: 6.08; 95% CI: 2.20,16.84; p=0.001). Conclusion: The newly developed questionnaire has been proven to be valid and reliable for assessing scuba divers' KAP in safety and emergency response. Scuba divers possess good knowledge, awareness, and practice in safety and emergency response, underscoring their commitment to safety. Dive-related injuries/illnesses among scuba divers were slightly lower than in the previous study, whereas the prevalence of mishaps was higher compared to earlier studies. Targeted group interventions have the potential to improve prevention and intervention strategies, providing efficient benefits to scuba divers.